1999
DOI: 10.1103/physrevd.59.054501
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis and the equivalent of a Thouless energy in lattice QCD Dirac spectra

Abstract: Random Matrix Theory (RMT) is a powerful statistical tool to model spectral fluctuations. This approach has also found fruitful application in Quantum Chromodynamics (QCD). Importantly, RMT provides very efficient means to separate different scales in the spectral fluctuations. We try to identify the equivalent of a Thouless energy in complete spectra of the QCD Dirac operator for staggered fermions from SU(2) lattice gauge theory for different lattice size and gauge couplings. We focus on the bulk of the spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…Recently, some progress was made in identifying the equivalent of the Thouless energy in QCD [19][20][21][22][23]. Again, we shall concentrate on the low-lying eigenvalues.…”
Section: Crossover To Non-universal Behaviormentioning
confidence: 99%
“…Recently, some progress was made in identifying the equivalent of the Thouless energy in QCD [19][20][21][22][23]. Again, we shall concentrate on the low-lying eigenvalues.…”
Section: Crossover To Non-universal Behaviormentioning
confidence: 99%
“…3. Independently of the spectral region considered [7] and of β we find that the point where the deviation sets in, scales as…”
mentioning
confidence: 98%
“…4). In order to find out, if these deviations are due to a Thouless energy, we performed a Fourier analysis of the oscillations of the staircase function [7]. From it we concluded that the deviations of the data obtained with polynomial unfolding are due to a non-polynomial-like part in the average level density and not to an equivalent of the Thouless energy.…”
mentioning
confidence: 99%
See 2 more Smart Citations